Uji Fisik Dan Mekanik Laminasi Kayu Akasia (Acacia Mangium) Menggunakan Perekat Epoxy - Malau, Natalia K; Sitompul, Iskandar R; Sandhyavitri, Ari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Timber can be used not only for daily purposes but also as structural requirements. The use of timber as a structural material is not only limited as solid timber, but also as a laminated timber. This aim is to determine of wood supplies of good quality and large dimension. This research determines the physical and mechanical properties of wood such as moisture content, density, bending test and shear test. Acacia mangium was used as the timber in this research and epoxy was used to glue each woods. Bending test was conducted on solid wood and solid wood with coating while shear test was carried out on solid wood, laminated wood, laminated wood with coating . All speciments used the same amount of epoxy 100 MDGL (Million Square Double Glue Line). From the test in this research it is found that average water content and density of acacia mangium was 8.51% and 0.825 gr/ respectively. Bending test carried out on solid wood and solid wood with coating resulted in the load of 72,67 N/ and 93,883 N/ respectively. Moreover shear test conducted solid wood, laminated wood, and laminated wood with coating resulted in the load of 2.129 N/ , 2.650 N/ and 1.919 N/ . Keywords : lamination, moisture content and density, bending test and shear test.